AA16, a new lytic polysaccharide monooxygenase family identified in fungal secretomes - Camille Filiatrault-Chastel; David Navarro; Mireille Haon; Sacha Grisel; Isabelle Herpoël-Gimbert; Didier Chevret; Mathieu Fanuel; Bernard Henrissat; Senta Heiss-Blanquet; Antoine Margeot; Jean-Guy Berrin (Biotechnology for Biofuels, 2019)
Abstract Background Lignocellulosic biomass is considered as a promising alternative to fossil resources for the production of fuels, materials and chemicals. Efficient enzymatic systems are needed to degrade the plant cell wall and overcome its recalcitrance. A widely used producer of cellulolytic cocktails is the ascomycete Trichoderma reesei, but this organism secretes a limited set of enzymes. To improve the saccharification yields, one strategy is to upgrade the T. reesei enzyme cocktail with enzymes produced by other biomass-degrading filamentous fungi isolated from biodiversity. Results In this study, the enzymatic cocktails secreted by five strains from the genus Aspergillus (Aspergillus japonicus strains BRFM 405, 1487, 1489, 1490 and Aspergillus niger strain BRFM 430) were tested for their ability to boost a T. reesei reference cocktail for the saccharification of pretreated biomass. Proteomic analysis of fungal secretomes that significantly improved biomass degradation showed that the presence of proteins belonging to a putative LPMO family previously identified by genome analysis and awaiting experimental demonstration of activity. Members of this novel LPMO family, named AA16, are encountered in fungi and oomycetes with life styles oriented toward interactions with plant biomass. One AA16 protein from Aspergillus aculeatus (AaAA16) was produced to high level in Pichia pastoris. LPMO-type enzyme activity was demonstrated on cellulose with oxidative cleavage at the C1 position of the glucose unit. AaAA16 LPMO was found to significantly improve the activity of T. reesei CBHI on cellulosic substrates. Conclusions Although Aspergillus spp. has been investigated for decades for their CAZymes diversity, we identified members of a new fungal LPMO family using secretomics and functional assays. Properties of the founding member of the AA16 family characterized herein could be of interest for use in biorefineries.